PERTUMBUHAN DAN HASIL TANAMAN MENTIMUN (Cucumis sativus L) PADA BERBAGAI DOSIS PUPUK NITROGEN DAN KONSENTRASI PUPUK ORGANIK DI DESA BOLOPLERET JUWIRING KLATEN - suwarto suwarto; Pramono Hadi; Libria Widiastuti (AGROTECH Research Journal, 2020)
The study was conducted to determine the dosage of nitrogen fertilizers and organic fertilizer that most enhance the growth dan yield of cucumber plant. The research was conducted in November 2018 until January 2019, in Ngerni, sub-village Bolopleret, Juwiring sub-district,Klaten Regency with altitude of 100-200 m dpl. This study used a completely randomized design method (CRD) with 12 teratment combinations and repeated 3 times so that 36 units were obtained. The first factor was the nitrogen fertilizer (N) dose which consisted of 4 treatment levels: (1) without nitrogen fertilizer (N0), (2) nitrogen fertilizer dose as much as 1,5 grams/plant (N1), (3) nitrogen fertilizer dose as much as 3,0 grams/plant (N2),(4) nitrogen fertilizer doses is much as 4,5 grams/plant (N3). The second factor is the concentration of organic fertilize (S) which consists of 3 treatment: (1) without organic fertilizer (S0), (2)concentration of organic fertilizer 2cc/liter (S1), (3)concentration of organic fertilizer is 4cc/liter (S2). Data will be analyzed using an analysis of variance (ANOVA) and if there is a significant difference it will be further tested us a multiple range test (DMRT) with a 5% level. The result show that: (1) nitogen fertilizer has a very significant effect on the number of fruit per plant but no significant effect on the parameters of number of leaves,heigt of plant, weight of fruit, fresh weight of biomass and dry weight of biomass. The most number of fruit per plant was found in the treatment of nitrogen fertilizers as much as 4,5 grams/plant (N3) namely 8,67 fruits, while the least amount was treated without nitrogen fertilizer (N0) is 4,67 fruits, (2) concentrations of organic fertilizers had a very significant effect on the parameters of the number of leaves, fresh weight of biomass and dry weight of biomass, had a significant effect on the number of fruits per plant but did not significantly affect plant height and fruit weight, (3) combinations of nitrogen fertilizer and organic fertilizer did not significantly affect the parameters of number of leaves,heigh of plant, weight of fruit, number of fruit per plant, weight of biomass and weight of dry biomass. Keywords : nitrogen feltilizer, organic fertilizer,cucumber